Barriers and facilitators to women’s participation in farmer producer organizations: A qualitative study exploring women’s empowerment and collective efficacy in Jharkhand, India - Bhanjdeo, Arundhita (International Food Policy Research Institute, 2024)
Over the last decade in India, farmer producer organizations (FPOs) have emerged as a means of collectivizing smallholder farmers and providing them access to extension, innovation, and market services. FPOs that center women farmers, traditionally at a disadvantage vis-à-vis their male counterparts in access to resources and extension, can serve to enhance women’s agency and collective action in agricultural value chains. We used 59 key informant interviews and nine focus group discussions to examine the constraints to, and facilitators of, women’s and men’s participation in three women-only FPOs in Jharkhand, an eastern Indian state. Additionally, we study the gender and power dynamics in such FPOs and the potential of collective efficacy to enhance agricultural and empowerment outcomes. The FPO intervention we evaluated was supported by an NGO that provides FPO members with both agricultural and gender-based inputs to improve agronomic practices, market linkages, agricultural yields and profits, and the role of women both within the FPO and within their households and communities. In this paper, we provide contextual insights on ‘what works’ to empower women in this context. Women’s perceptions of the benefits from FPO membership were heterogeneous. Our qualitative analysis suggests a nuanced picture of women’s autonomy and decision-making within and outside their household, further shaped by women’s and men’s perception of shifts in women’s access to resources and services. The emerging lessons provide inputs for development implementers and policymakers to recognize diverse contextual barriers in designing FPO interventions to enable and enhance women empowerment outcomes. The research also contributes to the body of knowledge on local gender norms and understanding of empowerment.